The conscience of a liberal - Krugman, Paul R. (New York : W.W. Norton & Co., 2007)
Today's most widely read economist challenges America to reclaim the values that made it great. Here he studies the past eighty years of American history, from the reforms that tamed the harsh inequality of the Gilded Age to the unraveling of that achievement and the reemergence of immense economic and political inequality since the 1970s. Seeking to understand both what happened to middle-class America and what it will take to achieve a "new New Deal," Krugman has woven together a nuanced account of three generations of history with sharp political, social, and economic analysis. This book, written with Krugman's trademark ability to explain complex issues simply, may transform the debate about American social policy.--From publisher description.
1. The way we were -- 2. The long Gilded Age -- 3. The great compression -- 4. The politics of the welfare state -- 5. The sixties : a troubled prosperity -- 6. Movement conservatism -- 7. The great divergence -- 8. The politics of inequality -- 9. Weapons of mass distraction -- 10. The new politics of equality -- 11. The health care imperative -- 12. Confronting inequality -- 13. The conscience of a liberal -- Notes -- Acknowledgments -- Index.
Includes bibliographical references (p. 275-284) and index.
Keywords: Income distribution -- United States; Equality -- United States; United States -- Economic conditions; United States -- Politics and government; United States -- Social policy